Effects of Fishmeal Substitution with House Cricket Meal (Acheta domesticus) on Productive Performance and Nutrient Metabolism of Blue Tilapia (Oreochromis aureus) - Aldo Fraijo-Valenzuela; Joe Luis Arias-Moscoso; Francisco Cadena-Cadena; Barbara Aboites-Martínez; Ramón Casillas-Hernández; Libia Zulema Rodriguez-Anaya; Pablo Gortáres-Moroyoqui; Jose Reyes Gonzalez-Galaviz (Fishes, 2026)
A 10-week feeding experiment was conducted to evaluate the effects of replacing fishmeal with cricket meal on the productive performance and transcriptional responses of genes related to nutrient metabolism and growth of blue tilapia (Oreochromis aureus). Five conventional tilapia feeds were formulated to replace fishmeal with cricket meal. Control diet (CD) was formulated with 20% fishmeal, and four diets gradually replaced fishmeal with cricket meal at 20, 40, 60, and 80% (D1–D4). A total of 200 fingerling tilapia (2.00 ± 0.09 g) were randomly distributed into 20 tanks (10 fish/tank), with four replicates per dietary treatment. The results showed that fish fed CD and D1 had higher growth performance values than those fed D2–D4. The feed conversion ratio (FCR) was significantly better in fish fed CD and D1 compared with fish fed D2–D4. The survival rate was similar for all treatments. The transcriptional response of genes related to nutrient digestion, absorption, and transport; lipid metabolism; and the somatotropic axis was marked downregulated in fish fed D2 and D4, whereas in fish fed D3, it exhibited a unique compensatory regulation across most pathways, likely sustained by its higher dietary lipid content. Although cricket meal did not prevent the metabolic effects associated with high soybean meal inclusion, survival remained high across all treatments. Cricket meal can replace up to 20% of the fishmeal in the feed for blue tilapia fingerlings, with soybean meal as the main protein source.